Detection of immovable objects on visually impaired people walking aids - Abdurrasyid, Abdurrasyid; Indrianto, Indrianto; Arianto, Rakhmat (Telkomnika, 2019)
In addition some ETA technology using the imaged based recognition such as the use of 3D-CMOS to detect object by the image capture sensor however can not recognize detail object [13], RGB-D image-based detection of stairs, pedestrian crosswalks and traffic signs [14], and to help blind persons read text labels and product packaging fromhand-held objects in their daily lives [15] However, from the result of the research, the equipment fails to recognize some objects, like stairs, a bump, or a hole. Images taken by the camera will be processed using Template Matching method have been used with great success over the years as image processing method [16], this method used to recognize obstacles and suggest a sign that should be performed by the user, this method have several benefits such as low storage requirements and its effectiveness when the amount of training data is limited [17], furthermore this method accurate enough to detect objects but no one has used this method on walking aids to help the blind, although this method has been used to identify boards of Scots pine to enables tracking of individual boards through an industrial process [18], Rajithkumar and Mohana used the algorithm to recognized the stone Inscripted Kannada Characters of Different Time Frames Based on Correlation Analysis [19], Bao used template matching algorithm to recognize the object of cucumber where this method is embedded on the harvesting robot [20], Pham used the method for object recognition in infrared video sequences [21], and Principi used the method to so based on some literature review above it can be said that this research has novelty in science on how the template matching method can be effectively used to help people to identify and recognize some silent objects. 2.Research Method The research was conducted in several illustrated phases, such as: user requirement collection, literature study, hardware design formation, implementation of design results, trials, and conclusions. After it gets the picture, then the template matching method works. the work procedure of the template matching method is by comparing the pixels from the picture taken with the pictures on the data training database so that the comparison result will out; the smaller the SAD value, the more similar the objects compared. [...]it will recognize the object that is being detected. The formula of the Template Matching method is written in (1) where SAD is Sum of Absolute Difference measure, A pixel in the search image with coordinates has intensity and a pixel in the template with coordinates has intensity . [...]the absolute difference in the pixel intensities is defined as Diff (xs,ys,xt,yt) = | Is (xs,ys) - It(xt,yt) | [22].